Central role of G protein Gαi2 and Gαi2+ vomeronasal neurons in balancing territorial and infant-directed aggression of male mice - Trouillet, Anne-Charlotte (2019)
Fil: Trouillet, Anne-Charlotte. University of Tours. Institut Français du Cheval et de l’Equitation. Institut National de la Recherche Agronomique. Laboratoire de Physiologie de la Reproduction et des Comportement; Francia